Pendugaan Umur Simpan Wajik yang Dikemas dengan Kertas Minyak dan Edible Film Tapioka Menggunakan Metode Akselerasi - Elsa Novitasari; Fajar Restuhadi; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The purpose of this research was to estimate the shelf life of wajik that is packed with oil paper and tapioca edible film. Estimation of shelf life using the acceleration method by storing wajik for 30 days at three different temperatures, there are temperatures of 30°C, 35°C, and 40°C. The parameters observed during the storage process were sensory assessments of rancidity and thiobarbituric acid (TBA) values of wajik. Data were analyzed using linear regression and the equations obtained were used to calculate the shelf life of wajik at normal temperature, which is 29°C. The wajik shelf life packed with oil paper based on rancidity sensory test is 29.787 days on the zero order reaction with the regression equation y = -2225.17x + 5.0060, with an activation energy value (Ea) of 4419.188 kal.mol-1, and the value of quality degradation (k) is 0.094 quality unit per day, while the wajik shelf life based on the TBA value test is 27.294 days on the first order reaction with the regression equation y = -3164.10x + 6.7644, with an activation energy value (Ea) of 6283.903 kal.mol-1, and the value of quality degradation (k) is 0.022 quality unit per day. The wajik shelf life packed with tapioca edible film based on rancidity sensory test was 45.455 days on the zero order reaction with the regression equation y = -3444.46x + 8.6946, with an activation energy value (Ea) of 6840.698 kal.mol-1, and the value of quality degradation (k) is 0.066 quality unit per day, the wajik shelf life based on the test TBA value is 32.234 days on the first order reaction with the regression equation y = -1086.80x - 0.0582, with the activation energy value (Ea) of 2158,385 kal.mol-1, and the value of quality degradation (k) is 0.026 quality unit per day. Keywords: Edible film, oil paper, shelf life, wajik.